Production of monoclonal antibodies to the cuticle of advanced third-stage larva of Gnathostoma spinigerum - Dantrakool A. (2014)
This study has demonstrated that sera from Balb/c mice infected with live advanced third-stage larvae (aL3), but not those immunized with crude larval extract, immunoprecipitated the 25-kDa protein from surface-iodinated extract of aL3. Hybridoma cell lines derived from spleen cells of an infected mouse secreted antibodies that reacted with several tissue of aL3 including the esophagus, intestine, muscle and cuticle by immunofluorescence assay. However, none of the cuticle-positive hybridoma cell lines produced antibodies that recognized surface-iodinated protein of aL3 by immunoprecipitation. Western blot analysis showed that monoclonal antibodies (MAbs) secreted by clones derived from one of the cuticle-positive hybridoma lines recognized proteins of molecular weights ranging from 55-96 kDa. The MAbs most likely reacted with the collagenous component of the cuticle.